The effect of extratropical cyclones on satellite-retrieved aerosol properties over ocean - Grandey, B; Stier, P; Wagner, T; Grainger, R; Hodges, K (2011)
Extratropical cyclones may have a significant effect on column aerosol properties over ocean. European Centre for Medium Range Weather Forecasts (ECMWF) derived storm-centric composites of Moderate Resolution Imaging Spectroradiometer (MODIS) and Advanced Along-Track Scanning Radiometer (AATSR) aerosol optical depth and aerosol size parameters are produced for the North Atlantic and the South Atlantic oceans. It is found that retrieved aerosol optical depth and aerosol size both increase near the center of the composite extratropical cyclones. Using composites of ECMWF ERA-Interim reanalysis data, it is demonstrated that wind speed is a considerably more likely explanatory variable than relative humidity for the aerosol observations. A comparison of composites for both MODIS and AATSR, which uses a wind speed dependent sea-surface brightness model in the aerosol retrieval, suggests that although surface brightness effects may contribute towards some of the observations, wind speed dependent emission of sea salt also appears to make a significant contribution to the observed aerosol properties. © 2011 by the American Geophysical Union.